Proteomic analysis in nasopharyngeal carcinoma - Netto, Eduardo Martins Carlinhos (2018)
Nasopharyngeal carcinoma (NPC) is a particular type of head and neck cancer with a strong ethnic and enigmatic epidemiology that long puzzles the scientific society. Despite present all over the world, around 80% of all cases are in Asia where it is endemic, followed by low incidence regions in all other continents. Portugal has the second incidence in Europe for women, and third for men (Globocan 2012) among all European countries. Many efforts have been made to clarify and understand this unique geographic and epidemiologic distribution. The onset and evolution of nasopharyngeal carcinoma is a complex multi-stage process and may take a long time to occur. Although the molecular basis remains uncertain, we know that environmental factors, Epstein-Barr virus (EBV) infection and genetic susceptibility are considered to be the three major contributors. Further examination of these genes’ expression in each tumor revealed that around 93 oncogenes are up regulated in each tumor, while the mean number of TSGs down regulated was 109. In Portugal, the works of Souza & Breda have identified important polymorphism markers that may play a role in the onset and NPC development on the Portuguese northern region population. Despite the efforts made, the molecular mechanisms of NPC carcinogenesis and progression remains to be understood. In this regard, current omics methodologies offer a different approach to identify unique miRNAs and proteins that expression signatures associated with the cancer phenotype, reflecting the biological and pathological grade of the disease. Thus, the discovery of useful NPC biomarkers will lead to new diagnostic and prognostic tools. Meanwhile, the treatment of NPC has evolved in the past two decades. Since 2000, intensity modulated radiation therapy (IMRT) has been widely used to treat nasopharyngeal carcinoma. IMRT provides better dose delivery to the target while sparing the surrounding normal tissues while local control reaches 98% at 4 years24-28. At least one prospective randomized controlled trial showed its benefit in salivary protection in HNC. However, despite the excellent local control, 43% of patients will develop distant metastasis before 5 years and die25-26. In Portugal, IMRT is used at the Instituto Português de Oncologia de Lisboa (IPOLFG) since 2009 and represents the current standard of care for HNC RT, including NPC. Until now, several prognostic markers were identified and investigated for screening, and prognostic tools for NPC, have been purposed, particularly in Asia. However, to our knowledge, there are no validated identified markers to predict distant metastasis or outcome. Moreover, the studies exploring this subject have identified a population-based variety of biomarkers stressing an omic translation of NPC ethnic distribution. At the present work, this research explored formalin-fixed paraffin-embedded samples of biopsied nasopharyngeal carcinoma tumors via proteomic analysis. The aim is to describe a tumor profiling from the studied cohort and discover biomarkers to predict distant metastasis. Secondary endpoints are the discovery of biomarkers related to tumor radioresistance and treatment toxicity. Label-free quantitative mass spectrometry was able to identify 12 up-regulated proteins on early-stage primary tumors that were not present on advanced-stage primaries. Moreover, EBV and HSV co-infection was detected. No signs of HPV-related proteins were seen. Although the clinical outcomes of early and advanced primary tumors were identical, this can be attributed to the known effectiveness of intensive chemoradiation. Moreover, the difference in tumor profiling may reflect that those earlystage tumors could benefit from de-escalation protocols. We were able to detect the presence of a pool of 10 proteins related to distant metastases. Among them, the significant presence of interferon and tyrosine kinase proteins generates the hypothesis that they may represent therapeutic targets. Validation is needed.